Analisis Kinerja Keuangan menggunakan Metode Z-Score pada PT. Unilever Indonesia TBK Tahun 2020-2024 - Desty Putri Asih; Dalizanolo Hulu (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk for the 2020–2024 period using the Altman Z-Score method as a predictive model for potential bankruptcy. This study uses a quantitative descriptive approach utilizing secondary data taken from audited financial reports published by the IDX. Five financial ratios working capital to total assets, retained earnings to total assets, EBIT to total assets, market value of equity to book value of debt, and sales to total assets are calculated to obtain the Z-Score value each year. The results of the study indicate that throughout the observation period, PT Unilever Indonesia Tbk consistently recorded a Z-Score value higher than 2.99, indicating that the company is in a healthy condition and is not at risk of bankruptcy. Despite increases and decreases in several financial indicators, the overall Z-Score value indicates that the company is still able to maintain its financial stability amidst economic challenges during and after the COVID-19 pandemic.